ANALYSIS OF ORGANIC VEGETABLE PRODUCT PURCHASES ON CONSUMER BEHAVIOR IN DELI TUA DISTRICT - As’ad , Octasella Ainani; Astuti, Aulia Putri Dwi; Pratama, Harry; Rizqi, Fauzan (Institute of Computer Science (IOCS), 2024)
This study aims to analyze consumer behavior in purchasing organic vegetable products in Deli Tua District. Data collection was conducted through a survey with a purposive sampling technique on 14 respondents who met the criteria as organic vegetable consumers. Data were collected using an online questionnaire via Google Forms and analyzed using a quantitative descriptive analysis method. The results showed that the majority of organic vegetable consumers were young age groups under 30 years (57.1%), with a dominant education level of high school (64.3%), and most were women (57.1%). In terms of occupation, housewives dominated (42.9%) with the highest monthly income in the range of IDR 2,100,000-IDR 3,000,000 (42.9%). The highest purchase frequency was 2-3 times per month (42.9%). Consumer perceptions showed strong confidence in the safety and health benefits of organic vegetables, with 61.5% of respondents strongly agreeing that organic vegetables are safe to consume. The environmental concern factor was also the main motivation for purchasing, with 84.6% of respondents agreeing. This study revealed that the decision to purchase organic vegetables is based more on health and environmental awareness than on trends or lifestyle.